Comets beyond 4 au: How pristine are Oort nuclei?. Issue 4 (3rd May 2022) - Fulle, Marco; Lazzarin, M; La Forgia, F; Zakharov, V V; Bertini, I; Mazzotta Epifani, E; Ammannito, E; Buzzoni, A; Capria, M T; Carbognani, A; Da Deppo, V; Della Corte, V; et al.
ABSTRACT: The ESA mission Comet Interceptor will target an Oort or interstellar comet during its first approach to the Sun. Meanwhile, the Vera Rubin LSST Survey will observe hundreds of active comets per month beyond 4 au from the Sun, where water vapour pressure is expected to be too low to eject dust. We discuss observations of dust tails at heliocentric distances larger than 4 au in order to retrieve the physical parameters driving cometary activity beyond Jupiter by means of a probabilistic tail model, which is consistent with the activity model defining the gas coma parameters due to the sublimation of carbon monoxide, molecular oxygen, methane, ethane, and carbon dioxide since the activity onset at 85 au from the Sun. We find that: (i) All the observed dust tails are consistent with the adopted activity model; (ii) The tail fits depend on three free parameters only, all correlated to the nucleus size; (iii) Tail fits are always improved by anisotropic dust ejection, suggesting activity of Oort nuclei dominated by seasons; (iv) Inbound seasons suggest cometary activity before the ejection of protocomets into the Oort cloud, as predicted by the activity model; (v) Oort nuclei larger than 1 km may be characterized by a fallout up to ≈100 m thick deposited during ≈60 yr inbound; (vi) On the other side, Oort nuclei smaller than 1 km may appear more pristine than Jupiter Family Comets when observed at 1 au from the Sun.